Final year allied health profession, midwifery and nursing students’ attitudes towards interprofessional education - Nor Azura Azmi,; Faridah Mydin Kutty, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Evaluation of pre-qualifying interprofessional education (IPE) programmes is important in exploring its effectiveness. The University of the West of England Interprofessional Questionnaire (UWE IPQ) has been rigorously validated, yet few studies using this tool have been published. We aimed to explore the attitudes of final year allied health profession (AHP), midwifery and nursing students towards IPE in this study. Differences between students’ attitudes towards IPE according to gender, undergraduate programmes, academic background and experience were also explored. A total of 103 participants, AHP (n = 10), midwifery (n = 19) and nursing (n = 74) students took part in the study. This study design used a cross-sectional questionnaire survey, and was conducted within the Faculty of Health Sciences, University of Southampton. The validated UWE IPQ was administered to a volunteer sample of final year AHP, nursing and midwifery students in June 2010. Findings revealed that majority of the students rated their communication and teamwork skills (76.7%), interprofessional learning (74.8%) and interprofessional relationships (92.2%) positively, but they held negative attitudes towards interprofessional interactions (69.9%). Significant differences were found between participants’ attitudes towards interprofessional learning in relation to undergraduate programmes (p = 0.01) and prior working experience in health and social care (p = 0.03). IPE has shaped the students’ views regarding their collaborative learning and teamwork. Therefore, introducing IPE initiative from the beginning of the pre-qualifying stage at universities would motivate them to become interprofessional collaborative-ready professionals.